Information System Data Population in Gunung Panjang Samarinda Seberang - Sartina Ayu Lestari; Annafi Franz; Emil Riza Putra (Politeknik Pertanian Negeri Samarinda, 2022)
The development of technology today is getting faster. With the sophistication of today's technology, we can facilitate the work to be done. We can find the information we need and we can expand the communication network using advanced technology. Currently, population data collection in the government system can be said to be ineffective. Population data collection with a manual system can cause inefficient processing of population data and administrative services will take a longer time. This study uses two methods of data collection, namely: interviews (interviews) and observation. The system development used in this research is the Waterfall model, which starts with the analysis, design, coding, testing, and maintenance stages. The Gunung Panjang Village Population Data Information System was created using several programming languages, Hypert Text Markup Language (HTML), Hypertext Preprocessor (PHP), and Cascading Style Sheet (CSS). and MySQL. It can be concluded that the results of this study are an Information System for Population Data Collection in Gunung Panjang Village which can be used for processing population data and as a means of delivering information on Gunung Panjang Village through the website.